1983
DOI: 10.3354/meps011273
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of a storm on coastal infauna

Abstract: Effects of storms on benthic infaunal communities have thus far been inferred rather than documented; especially lacking are studies examining immediate effects. To this end, the water column and 2 subtidal benthic sites were sampled before and after Storm David in September 1979. There were large post-storm increases in the numbers of infaunal species and individuals in the water column, presumably due to turbulent benthic boundary conditions. At the benthic stations, there were no pre vs. post-storm differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
1
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 18 publications
0
38
1
2
Order By: Relevance
“…Sediments of the surf zone are usually environments of great hydrodynamic energy (Barros et al 2001) which translates in frequent changes in sedimentary composition and an exacerbated physical stress for the benthic fauna. In addition, hydrodynamic events associated with winter storms also affect the infauna by removing, mobilizing or burying established populations in any given area (Dobbs and Mozarik 1983;Probert 1984;Reiss and Kröncke 2005) and resuspending potential sources of food such as carrion (Chatzinikolaou and Richardson 2008); this may also lead to the disappearance of most of the macrofauna in such conditions (Carpentier et al 1997). In fact, the grain-size median at site D15 shifted to the medium sand fraction during February 1997 when strong storms happened in the area; on the contrary, the sediment was mostly composed by the fine and very fine sand fractions for most of the year (Moreira et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sediments of the surf zone are usually environments of great hydrodynamic energy (Barros et al 2001) which translates in frequent changes in sedimentary composition and an exacerbated physical stress for the benthic fauna. In addition, hydrodynamic events associated with winter storms also affect the infauna by removing, mobilizing or burying established populations in any given area (Dobbs and Mozarik 1983;Probert 1984;Reiss and Kröncke 2005) and resuspending potential sources of food such as carrion (Chatzinikolaou and Richardson 2008); this may also lead to the disappearance of most of the macrofauna in such conditions (Carpentier et al 1997). In fact, the grain-size median at site D15 shifted to the medium sand fraction during February 1997 when strong storms happened in the area; on the contrary, the sediment was mostly composed by the fine and very fine sand fractions for most of the year (Moreira et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sites where larvae are initially deposited may differ from sites where postlarvae eventually recruit into populations. As previously stated, after initial deposition, larvae or postlarvae may choose microenvironments within a given location, they may actively reject the location by swimming into the water column, they may choose to remain at the sediment surface to be resuspended, or resuspension may be involuntary, but in any case, the organisms could be transported to new locations regularly (Bell and Sherman 1980;Palmer and Brandt 198 1) or only during storms (Hogue 1982;Dobbs and Vozarik 1983), or they may accumulate passively around microtopographic structures (Eckman 1979(Eckman , 1983. Alternatively, larvae initially deposited over a large area may differentially survive in hospitable microenvironments within that locale.…”
mentioning
confidence: 99%
“…Experimental work has shown that deposition of terrestrial sediments, mimicking storm-induced depositions, can cause decreased diversity in estuaries (Norkko et al 2002, Lohrer et al 2004). Conversely, Dobbs & Vozarik (1983) reported no significant effect of a single storm event on the macrobenthos at a shallow subtidal study site, although the authors postulated that effects may have been more pronounced at more exposed sites.…”
Section: Introductionmentioning
confidence: 91%